Analisis Ketimpangan Pembangunan Daerah Di 34 Provinsi Indonesia - Nisa, Cholly Fatun; Arivina Ratih Yulihar Taher; Prayudha Ananta; I Wayan Suparta (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
Interregional development inequality remains an important issue in national development planning, especially in developing countries like Indonesia. Imbalances in fiscal capacity, resource access, and infrastructure between provinces lead to marked differences in development levels. This study analyzes the effect of Balancing Fund (DP), Labor Force Participation Rate (TPAK), and Foreign Direct Investment (FDI) on development inequality using the Jaime Bonet Index. The data used is panel data from all provinces in Indonesia during 2014-2023, analyzed using the Fixed Effect Model (FEM) method. The results show that DP and FDI have a negative and significant effect, while TPAK is not significant. The findings emphasize the need to optimize DP and increase foreign investment to promote equitable and inclusive development.